Climbing fiber coupling between adjacent Purkinje cell dendrites in vivo - Bengtsson, Fredrik; Jörntell, Henrik (Frontiers in Cellular Neuroscience, 2009)
Climbing fiber discharges within the rat cerebellar cortex have been shown to display synchrony, especially for climbing fibers terminating in the same parasagittal bands. In addition, Purkinje cells which have the smallest rostrocaudal separation also seem to have the highest degree of synchrony. But this has so far only been investigated for distances down to 250 μm. In the present study, we wanted to investigate whether Purkinje cells that are located immediately next to each other display a particularly pronounced synchrony in their climbing fiber discharges. To this end, we used a previously undescribed type of electrophysiological recording, a single electrode, loose patch, dual dendritic recording, from pairs of adjacent Purkinje cells in the decerebrated, non-anesthetized cat. From each recorded dendrite, this technique provided well isolated, unitary calcium spikes, which we found to have a spontaneous activity that was essentially identical with the pattern of spontaneous climbing fiber discharges. By calculating the coupling in firing between the adjacent dendrites, we found that most climbing fiber responses occurred independently of each other and that the probability of coupled discharges was less than 8%. These values are comparable to those obtained in previous studies for Purkinje cells located within the same parasagittal band and show that climbing fiber coupling within a microzone exists also in non-rodent mammalian species. However, since the degree of synchrony of climbing fiber discharge was not particularly pronounced in adjacent Purkinje cells, it seems unlikely that climbing fiber synchrony has pronounced systematic regional variations within the same microzone.